ESTABLISHMENT OF TOUR PACKAGES AND FEASIBILITY OF COSTS WITH NPV IN BARITO TOURISM VILLAGE IN MALANG DISTRICT - Medea Rahmadhani Utomo; Mangku Purnomo; Fitrotul Laili; Mochamad Sufi Chaqqi (Socio-Economics/Agribusiness Department, 2023)
Tourism is a driver of the economic sector and a solution for the government to increase economic development. Tourism is one of the important sectors in developing a country because it contributes to job creation and state income and promotes the prosperity of a country. The tourism sector has a multiplier impact on the regional economy. One is that it can help increase people's income and alleviate poverty. There are problems in efforts to develop tourism, and researchers make plans for developing tourist village areas by mapping the potential of tourist destinations and packaging in the form of tour packages. Planning for developing tourist areas in rural areas through innovation in making tour packages from the results of mapping tourism potential will boost regional economic growth and strengthen the community to carry out a sustainable development process. The research was conducted using mixed method analysis, namely descriptive qualitative, and quantitative. Calculation data for the design cost of promotion planning and marketing of tourism villages is calculated using financial feasibility analysis. Financial feasibility analysis is carried out by calculating the NPV (Net Present Value). The planning for packaging the Barito Village tour package is named